Detecting structural and functional neuroplasticity in elite ice-skating athletes - Zhang, K.; Liu, Y.; Liu, J.; Liu, R.; Cao, C. (Human Movement Science, 2021)
Using resting-state fMRI, this study investigated long-term ice-skating training related changes in elite ice-skating athletes and compared them to healthy age-matched non-athletes under resting-state conditions. Significant differences were found in both structural and functional plasticity. Specifically, elite ice-skating athletes showed higher gray matter volume in the posterior cerebellum, frontal lobe, temporal lobe, posterior cingulate, caudate, and thalamus. The functional plasticity changes were primarily concentrated in the posterior cerebellar lobe. Additionally, stronger connectivity between the posterior cerebellar lobe and fusiform gyrus was also found in elite ice-skating athletes. Overall, the results are consistent with other studies that concluded long-term professional motor skill training can cause structural and functional plasticity in the regions of the brain related to motor planning, execution, and supervision. Both structural plasticity and functional plasticity are primarily enhanced in the posterior cerebellum. These changes may be related to the outstanding capability of speed and coordination caused by long-term ice-skating training. Present results add new evidence and may help us to understand the neural mechanisms of long-term motor skill training.